Evaluation of the efficiency of a low-cost aerator and water quality in intensive production systems of tilapia with bioflakes at different stocking densities (Research, Society and Development, 2021)
Among the types of production systems applied in aquaculture, the biofloc culture system (BTF) has been gaining space due to its sustainable techniques. Noteworthy is the low or zero renewal of water, the formation of the microorganism population predominantly autotrophic and heterotrophic, resulting in microbial flakes. Taking into consideration the effectiveness of the system in tilapia farming, this work aimed at the fabrication, implementation, and analysis of the efficiency of a low-cost aerator. To evaluate and control the physical and chemical parameters of the water, 3,780 Nile tilapia fry were used with an initial average biomass of 3±0.5g, distributed in 24 rectangular tanks with a useful volume of 125 liters. The experiment included 6 treatments (T1: 360 fish m-3, T2: 1800 fish m-3, T3: 1080 fish m-3, T4: 1440 fish m-3, T5: 720 fish m-3 and T6: 2160 fish m-3) and four repetitions. The efficiency of the Venturi effect aerator and the water quality parameters were analyzed. Comparisons of the averages were performed using Tukey's test at 5% significance. From the dissolved oxygen analysis, it was possible to conclude that the aerator Venturi effect was efficient during the experiment, meeting the desired levels, also taking into consideration the ease of applicability and low cost for its development. Through the analysis of the physical-chemical parameters of the water and the mortality rates during the experiment, it can also be concluded that the safest density to operate using the bioflocci is up to 720 fish m-3.